An Analysis of the Role of Rice Storage in Market Price Stabilization at Perum BULOG Meulaboh Branch - Fauzan, Ad; Wahyuninggsih, Yayuk Eko; Hartini, Hartini; Noviar, Helmi; Harmaini, Harmaini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The objective of this study is to evaluate the extent to which rice storage managed by Perum Bulog Meulaboh Branch contributes to stabilizing rice market prices. The data used in this study is secondary data covering the period from 2010 to 2024, obtained from Perum Bulog and the Central Statistics Agency (BPS). The method used in this research is simple linear regression analysis to measure the relationship between rice storage and rice market prices. The results of the analysis show that rice storage by Bulog has a significant impact on the stability of rice market prices, with a correlation coefficient of 0.910 and a coefficient of determination (R²) of 0.829. The t-test results show a t-value of 7.925 with a p-value of 0.000, indicating that rice storage significantly contributes to maintaining the stability of rice market prices. This study emphasizes the importance of managing rice storage as a key instrument in reducing market price volatility in Meulaboh.